2005
DOI: 10.1007/s10633-005-1983-x
|View full text |Cite
|
Sign up to set email alerts
|

ERG Oscillatory Potentials in Infants

Abstract: In young infants, the OPs are relatively immature compared to the photoreceptor responses, with the immaturity of the scotopic responses being more marked than that of the photopic responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 40 publications
5
17
0
1
Order By: Relevance
“…In the present study, OPs could not be recorded in some infants. This is consistent with the results of Westall et al [16] and Moskowitz et al [17], whose research showed that in early infancy, OPs were the most immature of the ERG responses, although the rate of development thereafter exceeded that of the other responses such that OPs amplitudes were within adult levels by 2 years of age. The amplitude ratio b/a derived from the combined response and had been used as an index of the relative maturation of outer and inner retinal elements [18,19].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, OPs could not be recorded in some infants. This is consistent with the results of Westall et al [16] and Moskowitz et al [17], whose research showed that in early infancy, OPs were the most immature of the ERG responses, although the rate of development thereafter exceeded that of the other responses such that OPs amplitudes were within adult levels by 2 years of age. The amplitude ratio b/a derived from the combined response and had been used as an index of the relative maturation of outer and inner retinal elements [18,19].…”
Section: Discussionsupporting
confidence: 93%
“…Thus, the BGL and readaptation properties of the neuronal adaptive system in terms of the OPs seem to be relatively more immature than those of the photoreceptor response as reflected in the awave. These findings correspond with previous reports that the OPs mature later than the photoreceptor response in rats as well as in humans (el Azazi & Wachtmeister 1990;Moskowitz et al 2005).…”
Section: Discussionsupporting
confidence: 93%
“…Although anatomically and physiologically different in several ways, the mixed rod/cone retina of the human and the rod-dominated rat retina show functional similarities of the inner retina (el Azazi & Wachtmeister 1990& Wachtmeister , 1991a& Wachtmeister ,b, 1993Moskowitz et al 2005;Akula et al 2007). At about 15 days of age, that is, after eye-opening, the ERG of the immature postnatal rat shows OPs of very low amplitudes as does the ERG of preterm infants (el Azazi & Wachtmeister 1990;Mactier et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In typical children, light-adapted OPs mature unevenly; OP2 and OP5 mature before OP3 and OP4 [38,43]. The present data show smaller OP amplitudes in the children's eyes that reached significance for all except the early maturing OP2.…”
Section: Discussionmentioning
confidence: 42%